2011
DOI: 10.1158/1055-9965.epi-11-0009
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Primary Non–Breast Cancer After Female Breast Cancer by Age at Diagnosis

Abstract: Background: Women diagnosed with breast cancer at young age have been shown to be at higher risk of developing a new primary cancer than women diagnosed at older ages, but little is known about whether adjustment for calendar year of breast cancer diagnosis, length of follow-up, and/or breast cancer treatment alters the risk pattern by age.Methods: We identified 304,703 women diagnosed with breast cancer during 1943 to 2006 in the Cancer Registries of Denmark, Norway, and Finland. Relative risks (RR) of subseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 24 publications
5
58
2
Order By: Relevance
“…While other Australian [10,26,27] and international studies [7-9, 11, 14] have documented elevated risks of MPCs for CRC survivors, especially at the same site, such studies have only presented crude risks for subsequent cancers without controlling for potential confounders. Literature on adjusted relative risk estimates for MPCs is sparse and, with the exception of a recent breast cancer study [28], tends to only quantify the risks of treatment-induced cancers [15,16,29]. To our knowledge, no study has previously reported adjusted relative risk estimates for MPCs in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…While other Australian [10,26,27] and international studies [7-9, 11, 14] have documented elevated risks of MPCs for CRC survivors, especially at the same site, such studies have only presented crude risks for subsequent cancers without controlling for potential confounders. Literature on adjusted relative risk estimates for MPCs is sparse and, with the exception of a recent breast cancer study [28], tends to only quantify the risks of treatment-induced cancers [15,16,29]. To our knowledge, no study has previously reported adjusted relative risk estimates for MPCs in Australia.…”
Section: Discussionmentioning
confidence: 99%
“…Several population-based cancer registry studies [6][7][8][9][10][11] as well as studies involving several cancer registries [12,13], have evaluated the risk of developing second primary cancers among women diagnosed with a first primary breast cancer with respect to the general population. Most of these studies were derived from European data [6][7][8][9][10][11][12][13] and from the National Cancer Institute's Surveillance, Epidemiology (SEER) cancer registries in the United States [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were derived from European data [6][7][8][9][10][11][12][13] and from the National Cancer Institute's Surveillance, Epidemiology (SEER) cancer registries in the United States [14][15][16]. However, risk estimates provided by these studies are largely different, with an overall excess risk ranging between 15 and 45% for all cancer sites combined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8,9] of ovarian cancer documented among estrogen receptor (ER)-positive breast cancer survivors aged <50 years is on average 21% higher compared to the expected number of ovarian cancers in the general population. [17] Since prophylactic BSO has been shown to dramatically reduce (up to 80-90%) the risk to develop ovarian cancer in women endowed with personal/familial risk factors as well as BRCA 1/2 gene mutation, [18,19] it could represent a valid clinical and cost-effectiveness option in the adjuvant treatment of pre-and perimenopausal hormone sensitive breast cancer patients, and an effective strategy for ovarian cancer prevention.…”
Section: Introductionmentioning
confidence: 99%